Low Complexity Deep-Decoder for OTSM With Hardware Impairments - Singh A.; Sharma S.; Sharma M.; Deka K. (My University, 2025)
Recently, the single-carrier modulation scheme orthogonal time-sequency multiplexing (OTSM) has emerged as an alternative to orthogonal time-frequency space (OTFS). By virtue of using Walsh-Hadamard transform, OTSM reduces modulation/demodulation complexity, with a performance similar to OTFS. However, the bit error-rate (BER) performance of OTSM deteriorates drastically in presence of transceiver hardware impairments (HIs), particularly with in-phase and quardature phase imbalance. In this letter, we develop a deep neural network based signal detector for OTSM (called DL-OTSM) to effectively compensate for HIs, with low decoding complexity. We extensively evaluate the performance of DL-OTSM with respect to variations in system parameters, including user mobility, HIs, frame size, and modulation order. Our results show that DL-OTSM achieves a significantly better BER performance compared to the state-of-the-art Gauss-Seidel method and conventional minimum mean-square error detector, regardless of HIs. © 1997-2012 IEEE.